Prevalence, causes, and correlates of traumatic dental injuries among seven-to-twelve-year-old school children in Dera Bassi - Rohini Dua; Sunila Sharma (Wolters Kluwer Medknow Publications, 2012)
Aim : The paper aims to present a study conducted in Dera Bassi, Mohali, India. The purpose of the study was to ascertain the prevalence of traumatic dental injuries (TDI) in children of age group 7-12 years in private schools in Gulabgarh village. Material & Method : Age & sex distribution, etiological factors, risk factors and cause of injury were the parameters taken into consideration. The data collected was processed and analyzed using the SPSS statistical software program. Results : The overall prevalence of dental trauma was 14.5%, amongst the 880 subjects examined, out of which, 63.2% males and 36.4% females were found to be affected. The maxillary central incisor was found to be most commonly affected tooth (43.8%). The most common cause of injury reported was fall during playing (37.5%). Conclusion : Enamel fracture was most prevalent (50%). No risk factor was significantly higher than others; however children with Angle's class II div 1 malocclusion exhibited greater risk factor for traumatic injuries.